APLIKASI PSIKOLOGI POSITIF DALAM DUNIA BISNIS - Juneman, Juneman (HUMANITAS (Jurnal Psikologi Indonesia), 2009)
This article exploits the application of positive psychology in business both on individual and group levels. Due to its recent emergence in Psychology and Business, the author will outline the definition of positive psychology, critics in this field as well as summary of the impacts of positive psychology. The highlight is given to the ´open source´ as a latest robust approach to be implemented in business. Further research that addresses some challenges related to the definition of happiness, psychometric measurement and the spectrum of impacts is outlined in the final section of the article.